De-risking maize commodity from climate induced risks across Ethiopian Agricultural Transformation Institute‘s Agricultural Commercialization Clusters (ACCs) in Ethiopia - Alemayehu, Sintayehu; Workeneh, Sintayehu; Terefe, Tadesse; Tesfaye, Lidya; Yaregal, Yodit (2024)
This project report focuses on the development and scaling of climate-smart agriculture (CSA) solutions for resilient agrifood systems in East and Southern Africa, particularly within Ethiopia's maize commercialization clusters. Key activities include identifying climate risks, validating CSA practices, and creating a gender-inclusive framework to ensure equitable benefits. A climate-smart credit scoring tool has been piloted to improve smallholder farmers' financial accessibility, integrating climate risk into creditworthiness assessment. Additionally, advisory frameworks and bundled solutions aim to provide smallholders with climate and weather information, CSA practices, and financial access to support sustainable agricultural productivity, resilience, and food security amidst climate variability​.